232k views
4 votes
HELP PLEASE
A sequence is defined by the rule f(n)=3f(n-1)+1. If f(1)=2 then f(3)=?

User TreDubZedd
by
6.0k points

2 Answers

4 votes
f(2)= 3f(1) +1 =3*2 +1 =7
f(3) =3 f(2) +1 =3*7 +1 =22
User Vincent Han
by
6.1k points
3 votes

Answer:

f(3) = 22

Explanation:

To find f(3), we need to first find f(2) since we have been given f(1) to be equal to 2.

f(n)=3f(n-1)+1

To find f(2), simply replace all the n in the function by 2

f(2) = 3f(2-1) + 1

=3f(1) + 1

but we were given f(1) to be equal to 2 from the question, so we will simply substitute f(1)=1 in the function

f(2) = 3f(1) + 1

=3(2) + 1

= 6 + 1

=7

so our f(2) = 7

We can now proceed to find f(3), to find f(3) simply replace all n by 3

f(3) = 3f(3-1) + 1

=3f(2) + 1

But we have gotten f(2) to be 7, so we simply substitute f(2) = 7 in the function.

f(3) = 3f(2) + 1

=3(7) + 1

=21 + 1

= 22

f(3) = 22

Therefore f(3) is 22

User Haris Anwar
by
5.8k points